Multi-Omics Integration Analysis Identifies Lipid Disorder of a Non-Alcoholic Fatty Liver Disease (NAFLD) Mouse Model Improved by Zexie–Baizhu Decoction - Cao, Yuhan; Shi, Jingying; Song, Luyao; Xu, Junjiu; Lu, Henglei; Sun, Jianhua; Hou, Jinjun; Chen, Jing; Wu, Wanying; Gong, Likun (Frontiers in Pharmacology, 2022)
Non-alcoholic fatty liver disease (NAFLD) is an increasingly epidemic metabolic disease with complex pathogenesis. Multi-target therapy may be an effective strategy for NAFLD treatment, and traditional Chinese medicine (TCM) characterized by multi-ingredients and multi-targets has unique advantages in long-term clinical practice. Zexie–Baizhu (ZXBZ) decoction is a Chinese classical formula to treat body fluid disorders initially. Although many bioactive monomers from Zexie and Baizhu had been discovered to improve lipid disorders, limited research studies were focused on the aqueous decoction of ZXBZ, the original clinical formulation. In the current study, we identified 94% chemical composition of ZXBZ decoction and first discovered its hepaprotective effect in a gubra-amylin NASH (GAN) diet-induced NAFLD mouse model. Based on metabolomics and transcriptomics analyses, we speculated that lipid and glucose metabolisms might be regulated by ZXBZ decoction, which was further confirmed by improved dyslipidemia and hepatic steatosis in ZXBZ groups. Consistently with cross-omics analysis, we discovered ZXBZ decoction could influence two energy sensors, Sirt1 and AMPK, and subsequently affect related proteins involved in lipid biosynthesis, catabolism, and transport. In conclusion, ZXBZ decoction regulated energy sensors, consequently impeded lipogenesis, and promoted fatty acid oxidation (FAO) to alleviate lipid disorders and protect the liver in NAFLD models, which suggested ZXBZ decoction might be a promising treatment for NAFLD.